REPRESENTASI PEREMPUAN GEN Z DALAM DRAMA SERI SUGAR DADDY DI PLATFORM VIU (Analisis Semiotika Roland Barthes) - Rizqiyah; Suratnoaji, Catur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of sugar relationships has increasingly been represented in digital media, including the Sugar Daddy drama series on the Viu streaming platform. Such representations shape public understandings of Generation Z women's identities and economic power relations. This study aimed to analyze the representation of Generation Z women's in the Sugar Daddy drama series. This research employed a qualitative approach using Roland Barthes' semiotic analysis through the levels of denotation, connotation, and myth. The data consisted of 23 selected scenes that were relevant to the research objectives. The findings showed that the series represented Generation Z women through two different identities those women who maintained their principles despite economic pressures and women who voluntarily viewed sugar relationships as material-based transactional relationships. The findings also indicated that economic power relations were represented through men's economic dominance, while female characters still retained the ability to make choices and negotiate the terms of their relationships. The myth analysis revealed that the series both reproduced and deconstructed social myths surrounding Generation Z women, age-gap relationships, and sugar relationships. This study concluded that the Sugar Daddy drama series represented Generation Z women's identities and economic power relations as socially constructed meanings that could not be understood solely through stereotypes existing in society.